2001
DOI: 10.1128/jcm.39.10.3678-3683.2001
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Active Lyssavirus Infection in Wild Bat Populations by Viral RNA Detection on Oropharyngeal Swabs

Abstract: Brain analysis cannot be used for the investigation of active lyssavirus infection in healthy bats because most bat species are protected by conservation directives. Consequently, serology remains the only tool for performing virological studies on natural bat populations; however, the presence of antibodies merely reflects past exposure to the virus and is not a valid marker of active infection. This work describes a new nested reverse transcription (RT)-PCR technique specifically designed for the detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
5
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 22 publications
4
69
5
3
Order By: Relevance
“…With more than 4000 oropharyngeal swabs and 1200 blood samples tested by RT-PCR and RFFIT, respectively, this is one of the most extensive active bat rabies surveillance studies ever conducted in Europe. While in several European studies no EBLVspecific RNA was detected in oropharyngeal swabs [6], we found seven oropharyngeal swab samples positive for EBLV-1 by RT-PCR which is in accordance with previous reports from Spain, UK and Switzerland [13,20,24,25]. The majority of RT-PCR-positive results were associated with E. serotinus bats, the natural reservoir host of EBLV-1.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With more than 4000 oropharyngeal swabs and 1200 blood samples tested by RT-PCR and RFFIT, respectively, this is one of the most extensive active bat rabies surveillance studies ever conducted in Europe. While in several European studies no EBLVspecific RNA was detected in oropharyngeal swabs [6], we found seven oropharyngeal swab samples positive for EBLV-1 by RT-PCR which is in accordance with previous reports from Spain, UK and Switzerland [13,20,24,25]. The majority of RT-PCR-positive results were associated with E. serotinus bats, the natural reservoir host of EBLV-1.…”
Section: Discussionsupporting
confidence: 92%
“…At the serotine bat colony level (Hartmannsdorf, Brandenburg) the percentage of qRT-PCR-positive swabs reached 4·7%. In contrast, up to 21% RT-PCR-positive results were reported from a Spanish serotine bat colony targeted after the detection of a bat rabies case during passive surveillance [24]. In our study, repeated detection of viral RNA in saliva swabs from recaptured serotine bats (E. serotinus) was not observed.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…With maternity colonies behaving as closed communities, a pattern of epidemiological circulation by fast-spreading viral waves-as is typical in other viruses-is unlikely to occur. In fact, given that E. isabellinus bats can survive after infection (Pérez-Jordá et al, 1995;Echevarría et al, 2001), vertical transmission within bat colonies (mother-offspring) would be the most likely way for the virus to spread, with only occasional transmission between colonies caused by individual interactions between females and males (for example, mating) at the end of the reproductive season and when maternity colonies disaggregate. Although EBLV-1 has not yet been found in Africa (only around 50 E. isabellinus tested to date), we predict that Eptesicus from Northern Morocco will also carry the rabies virus and that its strains will be very similar to the EBLV-1 rabies strains found in Andalusia.…”
Section: Table 3 Migration Rate (M) Between Regionsmentioning
confidence: 99%
“…Although FAT is the gold standard assay for the identification of lyssavirus in tissues, in recent years advances in molecular diagnostics have seen wide use of conventional and realtime RT-PCR for the diagnosis of lyssavirus infections (Banyard et al, 2009;Black et al, 2002;Echevarría et al, 2001;Foord et al, 2006;Smith et al, 2002 Until recently, the only cases of lyssavirus infection recorded in Australia were in bats and humans. However, in May 2013 two horses were diagnosed with ABLV and are the first confirmed Australian field infections.…”
mentioning
confidence: 99%